The Principal's Function as an Academic Supervision Planner in the East Kalimantan Province of Indonesia's Implementation of the Integrated Islamic School Network's Curriculum - Warman; Utari, Tria Ina (Universitas Lancang Kuning, 2023)
Although numerous countries have conducted studies on the function of school principals as supervisors, some principals, instructors, and even supervisors lack a thorough understanding of academic supervision. In the Province of Indonesian East Kalimantan, this study intends to examine the principal's function as a planner for academic supervision in the implementation of the Integrated Islamic School Network (JSIT) curriculum. The headmaster, a vice principal, and two teachers were all participants in the qualitative interview process used in this study. Thematic and interpretive analysis was done on the interview data. According to research findings, the JSIT curriculum was implemented successfully in the province of East Kalimantan by using school principals as academic supervision planners. Compiling the program, compiling and scheduling the implementation of academic supervision, and creating supervision tools in accordance with the JSIT curriculum are the three stages that make up the planning process